La oruga muy hambrienta - Carle, Eric. (New York : Scholastic Inc., 1989)
Follows the progress of a hungry little caterpillar as he eats his way through a varied and very large quantity of food until, full at last, he forms a cocoon around himself, goes to sleep, and awakens as a beautiful, colorful butterfly.
Translation of: The very hungry caterpillar.
Keywords: Toy and movable books; Caterpillars; Butterflies; Spanish language -- Reading (Elementary)